Análise de crescimento em Heteranthera reniformis, sob diferentes teores de Ca, Mg e S - Domingos, Vanessa David [UNESP]; Martins, Dagoberto [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Costa, Neumarcio Vilanova da [UNESP]; Paschoa, Paulo Lovo de [UNESP] (Instituto Agronômico de Campinas, 2006)
O objetivo deste trabalho foi estudar o crescimento, alocação de biomassa e teores de nutrientes em Heteranthera reniformis Ruiz & Pav., sob o efeito de diferentes concentrações de Ca, Mg e S. As plantas foram cultivadas em vasos plásticos preenchidos com pedra rolada, em soluções nutritivas a 80% da concentração original de Sarruge, correspondente à solução-base. O experimento foi desenvolvido em delineamento experimental inteiramente casualizado, com quatro teores (0%, 25%, 50% e 75% da solução base de 80%) avaliados em Ca, Mg e S, além da testemunha (solução-base), com quatro repetições no período de 35 dias em casa de vegetação. O aumento dos teores de Ca na solução propiciou uma redução significativa na área foliar. As maiores áreas foliares ocorreram em soluções a 25% de Ca e 50% de Mg e S. A maior proporção de biomassa seca está no caule, exceto a 25% de Ca (40 mg L-1) que propiciou maior área foliar e área foliar específica. Entre os teores de Mg na solução, as maiores biomassas foram observadas a 50% de Mg (19,2 mg.L-1) e, para o S, não houve diferenças significativas, exceto a 0%. A solução com 160 mg L-1 de Ca propiciou maior concentração de Ca na folha (56,6 g kg-1). Os teores de Ca, Mg e S em solução corresponderam a um aumento proporcional na planta. Os teores de enxofre nas folhas e nos caules aumentaram com a concentração de S na solução, enquanto o teor nas raízes reduziu nas concentrações entre 12,8 e 38,4 mg.L-1.

The objective was to study the growth, biomass allocation and concentration of nutrients in Heteranthera reniformis Ruiz & Pav. under the effect of different concentrations of Ca, Mg and S. The plants were cultivated in plastic pots fulfilled with rolled stone, in nutrient solutions of 80% of the original concentration of Sarruge. The experiment was carried out in a complete randomized design, with 4 contents (0, 25, 50 and 75% of the base solution) evaluated in Ca, Mg and S, plus the control (100% of the solution base), with 4 replicates in the period of 35 days in greenhouse. The increase of contents of Ca produced significant reduction in the leaf. The largest areas leaf occurred in solutions of 25% of Ca and 50% of Mg and S. The largest proportion of dry biomass was found in the stem, except with 25% of Ca (40 mg.L-1) in solution that produced larger leaf area and larger specific leaf area. Among different Mg contents, larger biomasses were observed at 50% of Mg (19, 2 mg.L-1) and, for S, there were not significant differences, except at 0% of S in solution. The solution with 160 mg.L-1 of Ca produced the largest concentration of Ca in leaf (56, 6 g.kg-1). The contents of Ca, Mg and S in solution corresponded to a proportional increase in the plant. The contents of sulfur in leaves and in stems increased with the concentration of S, whereas the content in roots reduced in the concentrations between 12,8 and 38,4 mg.L-1.
Growth analysis in Heteranthera reniformis under different contents of Ca, Mg and S
Keywords: planta aquática; planta daninha; nutrientes e biomassa; Aquatic plant; weed; nutrients and biomass